The complete mitochondrial genome of Sinibrama taeniatus (Cyprinidae: Cultrinae). (3rd May 2016) - Li, Wei-Tao; Shao, Ke; Xiong, Mei-Hua; Yan, Shu-Xiang; Liao, Xiao-Lin; Que, Yan-Fu
Abstract: In this study, the complete mitochondrial DNA genome sequence of Sinibrama taeniatus was first determined by DNA sequencing based on the PCR fragments. The complete mitochondrial DNA (mtDNA) genome sequence of S. taeniatus was a circular molecule of 16, 623 bp in length. It consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region (D-loop). The gene nucleotide composition of S. taeniatus was 31.3% A, 26.8% C, 16.1% G, and 25.8% T, with a relatively high A + T content (57.1%). The results could provide useful data for studying genetic diversity and phylogenetics in S. taeniatus and related species.